To flee or not to flee: detection, avoidance and attraction of profitable resources by Daphnia magna studied with olfactometer - Johann P. Müller; David Laloi; Claude Yéprémian; Cécile Bernard; Florence D. Hulot (Journal of Limnology, 2013)
The cladoceran herbivore Daphnia magna is a major consumer of phytoplankton in lakes. Therefore, this organism may control the phytoplankton community and the proliferation of some algae or cyanobacteria. Cladoceran behaviour and migration in relation to temperature, light or presence of planktivorous fishes have been well studied. In particular, it is known that the detection of kairomones produced by predators may induce avoidance. Avoidance could also occur with other semiochemicals such as cyanotoxins. In order to explore this hypothesis, we used an olfactometer to observe and measure the exploratory behaviour of D. magna individuals based on the motivation for food. Daphnids were allowed to choose between different compounds: water, a pure cyanotoxin, i.e. the microcystin-RR [(MC)-RR], extracts of one MC-producing strain (PMC 75.02) and one MC-free strain (PMC 87.02) of Planktothrix agardhii, or a green algae Scenedesmus obliquus. With this experimental design, we observed that i) cladocerans are able to detect resources with different qualities, ii) they can explore before exhibiting preferences, and iii) daphnids are able to avoid compounds that are potentially toxic (e.g., microcystins). First, daphnids explored the environment, subsequently (after about 1.5 h), they showed a significant tendency to stay where there is a profitable resource such as S. obliquus. These results also suggest that specimens of D. magna cannot detect MC compounds from P. agardhii, but they respond to it as a food resource. The study of zooplankton ability to explore the environment when exposed to semiochemicals needs further investigation.